Mediterranean–Black Sea gateway exchange: scientific drilling workshop on the BlackGate project - Krijgsman, Wout; Vasiliev, Iuliana; Beniest, Anouk; Lyons, Timothy; Lofi, Johanna; Tari, Gabor; Slomp, Caroline P.; Cagatay, Namik; Triantaphyllou, Maria; Flecker, Rachel; Palcu, Dan; McHugh, Cecilia; et al. (Copernicus GmbH, 2022)
Abstract. The MagellanPlus workshop “BlackGate” addressed fundamental questions concerning the dynamic evolution of the Mediterranean–Black Sea (MBS) gateway and its palaeoenvironmental consequences. This gateway drives the Miocene–Quaternary circulation patterns in the Black Sea and governs its present status as the world's largest example of marine anoxia. The exchange history of the MBS gateway is poorly constrained because continuous Pliocene–Quaternary deposits are not exposed on land adjacent to the Black Sea or northern Aegean. Gateway exchange is controlled by climatic (glacio-eustatic-driven sea-level fluctuations) and tectonic processes in the catchment as well as tectonic propagation of the North Anatolian Fault Zone (NAFZ) in the gateway area itself. Changes in connectivity trigger dramatic palaeoenvironmental and biotic turnovers in both the Black Sea and Mediterranean domains. Drilling a Messinian to Holocene transect across the MBS gateway will recover high-amplitude records of continent-scale hydrological changes during glacial–interglacial cycles and allow us to reconstruct marine and freshwater fluxes, biological turnover events, deep biospheric processes, subsurface gradients in primary sedimentary properties, patterns and processes controlling anoxia, chemical perturbations and carbon cycling, growth and propagation of the NAFZ, the timing of land bridges for Africa and/or Asia–Europe mammal migration, and the presence or absence of water exchange during the Messinian salinity crisis. During thorough discussions at the workshop, three key sites were selected for potential drilling using a mission-specific platform (MSP): one on the Turkish margin of the Black Sea (Arkhangelsky Ridge, 400 m b.s.f., metres below the seafloor), one on the southern margin of the Sea of Marmara (North İmrali Basin, 750 m b.s.f.), and one in the Aegean (North Aegean Trough, 650 m b.s.f.). All sites target Quaternary oxic–anoxic marl–sapropel cycles. Plans include recovery of Pliocene lacustrine sediments and mixed marine–brackish Miocene sediments from the Black Sea and the Aegean. MSP drilling is required because the JOIDES Resolution cannot pass under the Bosporus bridges. The wider goals are in line with the aims and scope of the International Ocean Discovery Program (IODP) “2050 Science Framework: Exploring Earth by Scientific Ocean Drilling” and relate specifically to the strategic objectives “Earth's climate system”, “Tipping points in Earth's history”, and “Natural hazards impacting society”.
Keywords: Allgemeine Geologie; QE1-996.5; SDG 14 – Leben unter Wasser; Drilling; Geology; Mediterranean; [SDU] Sciences of the Universe [physics]; Black sea; [SDU]Sciences of the Universe [physics]; SDG 13 – Maßnahmen zum Klimaschutz; SDG 13 - Climate Action; SDG 14 - Life Below Water; Black gate; General geology